KARAKTERISASI LERENG BERPOTENSI LONGSOR SERTA UPAYA MITIGASI BENCANANYA: STUDI KASUS DI BADAN JALAN LEMBANG DAN CIJAMBE-SUBANG - Aditya Angga; Selly Feranie; Adrin Tohari; Foureier D. E. Latief (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2016)
Landslide is one of often phenomenon which consist in Indonesia and specially for region West Bandung District and Subang. Landslide has divided into two main part that are landslide slip and landslide soil erosion. One of some methods for characteization of soil properties are geotechnical method. Five slopes which potentially slope in Cirangkong Village, Cijambe Subdistrict (cjb1, cjb2, cjb3), Subang District (sbg), and Lembang (lbg), West Java have characterized by used geotehnical method for identifies soil magnitude of slip area and soil erosion substance. The result of physicsal properties characterization e.g cohesion, displacement angle, unit weight and geometry of potential valanche slope have resulted from analysis slope stability used for predicting soil range (run-out) and soil velocity according to use simple Coulomb method. Run-out predicting result and soil center of mass velocity from five slopes there are cjb1, cjb2, cjb3, lbg and sbg respectively are 1,22 m and 6,78 m/s, 0,97 m and 5,76 m/s, 0,48 m and 3,45 m/s, 1,07 m/s and 4,83 m/s, 1,57 m and 5,93 m/s. If landslide happen, soil erosion will be cover the way. From that characterization, derivated the efforts mitigation which observe from increasing slope safety factor (FK>1,25) Keyword: slope stability caracterization, run-out, mitigation.